Penehyclidine in prevention of postoperative nausea and vomiting: a systematic review and meta-analysis of randomized controlled trials - Lu, Jia-Chao; Chen, Yanjun; Lai, Lan; Shen, Qi-hong (Frontiers in Medicine, 2025)
BackgroundPostoperative nausea and vomiting (PONV) are prevalent complications following general anesthesia. The effectiveness of penehyclidine (PHC) in reducing PONV is still debated. To address this issue, we conducted this systematic review and meta-analysis to assess both the effectiveness and safety of PHC in preventing PONV after general anesthesia.MethodsTo gather relevant studies on PHC use for preventing PONV, six electronic databases (PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, and Wanfang Database) and trial registries were searched. Placebo-controlled trials that explored the effect of PHC on PONV in patients undergoing general anesthesia were included. The primary outcome was the incidence of PONV. Adverse events were evaluated to explore the safety of PHC. This meta-analysis was carried out using Review Manager 5.3. Risk of bias for included studies was assessed using the Cochrane risk of bias tool 2.0. Quality of evidence was assessed using Grading of Recommendations Assessment, Development, and Evaluation. Heterogeneity was explored by subgroup analyses. Publication bias was evaluated by funnel plot analysis. Additionally, trial sequential analysis was used to reduce the risk of type I error.ResultsThis analysis included ten randomized controlled trials with 1,427 participants. The PHC group showed a significantly lower incidence of PONV compared to the control group (risk ratio = 0.48, 95% confidence interval [0.36, 0.65]; p < 0.05, I2 = 68%). A reduction in postoperative nausea, vomiting, and the need for rescue antiemetic therapy was also associated with PHC.ConclusionOur research suggests that PHC might be a new option for preventing PONV after general anesthesia.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, CRD42022355743.